2000
DOI: 10.1038/modpathol.3880138
|View full text |Cite
|
Sign up to set email alerts
|

Hyperplastic-Like Mucosal Change in Crohn's Disease: An Unusual Form of Dysplasia?

Abstract: Patients with Crohn's disease are at increased risk of developing intestinal adenocarcinoma. Dysplasia is both a marker and a precursor of adenocarcinoma in this setting. In a review of our cases of Crohn's-related adenocarcinoma, we noted a peculiar hyperplastic-like mucosal change (HPC) in mucosa both adjacent to and distant from the adenocarcinoma in some cases. However, the significance of this change is unknown.We evaluated 30 cases of Crohn's-related adenocarcinoma and 30 age-and site-matched resection s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 21 publications
3
37
0
Order By: Relevance
“…IBD includes Crohn's disease (CD) and ulcerative colitis (UC); each affects approximately one in a thousand people in Western countries. Although CD and UC may have different genetic origins and affect different areas of the gastrointestinal tract, both diseases result in an increased risk of cancer compared with the age-matched general population (10,11). Clearly, chronic inflammation contributes to carcinogenesis in the gastrointestinal tract; however, the mechanisms are not understood.…”
Section: Introductionmentioning
confidence: 95%
“…IBD includes Crohn's disease (CD) and ulcerative colitis (UC); each affects approximately one in a thousand people in Western countries. Although CD and UC may have different genetic origins and affect different areas of the gastrointestinal tract, both diseases result in an increased risk of cancer compared with the age-matched general population (10,11). Clearly, chronic inflammation contributes to carcinogenesis in the gastrointestinal tract; however, the mechanisms are not understood.…”
Section: Introductionmentioning
confidence: 95%
“…At this point in time, 3 morphologic subtypes of dysplasia in IBD have been described, all of which may exhibit flat or polypoid architecture: intestinal dysplasia, which cytologically resembles dysplasia seen in sporadic adenomas, hypermucinous/villous dysplasia, and serrated dysplasia [2,3,[6][7][8]. Polypoid serrated dysplasia resembling sporadic serrated polyps has also been observed in IBD patients [6,[8][9][10].…”
Section: Introductionmentioning
confidence: 97%
“…Rubio et al 16 described higher rates of dysplastic serrated lesions near carcinomas in resection specimens from inflammatory bowel disease patients compared with non-inflammatory bowel disease patients. Kilgore et al 15 reported non-dysplastic serrated lesions in 33% of cancer-bearing resection specimens from patients with Crohn's disease compared with 10% of controls without cancer. Srivastava et al 17 described patients with longstanding inflammatory bowel disease and multiple hyperplastic polyps and sessile serrated adenoma/polyps (reminiscent of the serrated polyposis syndrome), nearly half of which contained KRAS but not BRAF mutations.…”
Section: Modern Pathology (2015) 28 1584-1593mentioning
confidence: 99%
“…9,[11][12][13] Nonetheless, recognition of the full range of histologic lesions with malignant potential in the setting of inflammatory bowel disease is incomplete. Although several prior studies have described serrated colorectal lesions in patients with inflammatory bowel disease, [14][15][16][17] a systematic characterization of serrated polyps in this population has not been hitherto reported. We hypothesized that serrated polyps in patients with inflammatory bowel disease may have similar biologic characteristics to sporadic serrated polyps and therefore undertook a retrospective review of colorectal serrated polyps diagnosed over a 14-year period among inflammatory bowel disease patients undergoing routine colonoscopic surveillance at our institution.…”
mentioning
confidence: 99%